PRARANCANGAN PABRIK GASIFIKASI BATUBARA KAPASITAS 400.000 TON/TAHUN - , AGHNIA GRANITTIA BAKHRI; , Ir. Hary Sulistyo, SU., Ph.D. ([Yogyakarta] : Universitas Gadjah Mada, 2014)
Most of the people of Indonesia used the energy that comes from fossil fuels for example oil, gas and coal. The low rank coal by gasification technology is one of the efforts to increase the use of coal to produce a product that is easily converted into a variety of energy sources and raw materials of chemical industry. Development opportunities of coal gasification industry in Indonesia is quite large. The plant is planned to operate for 330 days / year with a coal input capacity of 400.000 tons / year. The main raw material required is as much as 50.505 kg/hour of coal and 27.000 kg/hour of carbondioxide. The method used is the coal gasification. In general, syngas manufacturing stages process is as follows: (i) reaction between coal and carbondioxide with steam with reactor fluidized bed gasifier, (ii) separation of gas mixture and solid, (iii) syngas purification with absorber. As a support, utility plant unit supplies the cooling water as much as 2.941.088,26 kg / hour, 11.209,41 kVA electricity, compressed air up to 108 m 3 /hr, and 127.051,78 kg / hoursteam. The plant will be established in the city of Berau, East Kalimantan province, with consideration of raw material oriented. Berau region close to the coal industry. Plant location close to the river, so that the source of water for utility plant unit derived from river water. Calculation of economic evaluation results is fixed capital required equal to $36.773.844,54 + Rp 294.174.088.118,73 and working capital equal to $ 25.604.779,57 + Rp 33.143.004.393.263,39. At 100% production rate, obtained ROI before tax of 27,60 %, ROI after tax of 13,80 %, POT before tax of 2,66 years, POT after tax of 4,20 years, with BEP at 49,61 %, SDP at 27,69 %, and 26,5 % for DCFRR. Based on consideration of the economic evaluation results, this coal gasification plant with capacity 400.000 tons / year worth to be studied further.